2004
DOI: 10.1210/rp.59.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Essential Roles of Her2/erbB2 in Cardiac Development and Function

Abstract: The tyrosine kinase receptor erbB2, also known in humans as Her2, is a member of the epidermal growth factor receptor (EGFR or erbB1) family, which also includes erbB3 and erbB4. The erbBs were discovered in an avian erythroblastosis tumor virus and exhibited similarities to human EGFR (Yarden and Sliwkowski, 2001). Her2/erbB2 is highly expressed in many cancer types. Its overexpression is correlated with a poor prognosis for breast and ovarian cancer patients. ErbB receptors bind to a family of growth factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(137 citation statements)
references
References 35 publications
6
123
0
5
Order By: Relevance
“…have been developed to target specifically tumor cells expressing ErbB2 oncoprotein. These strategies include chemical inhibitors (61), dominant kinase-negative mutants (38,62), monoclonal antibodies (63,64), and antisense gene inhibition (65). However, these strategies have been focused mainly on ErbB2 overexpressing tumor cells.…”
Section: Erbb2/erbb3 Heterodimer Formation and Erbb3 Activation-hetermentioning
confidence: 99%
See 1 more Smart Citation
“…have been developed to target specifically tumor cells expressing ErbB2 oncoprotein. These strategies include chemical inhibitors (61), dominant kinase-negative mutants (38,62), monoclonal antibodies (63,64), and antisense gene inhibition (65). However, these strategies have been focused mainly on ErbB2 overexpressing tumor cells.…”
Section: Erbb2/erbb3 Heterodimer Formation and Erbb3 Activation-hetermentioning
confidence: 99%
“…Gene amplification and overexpression of ErbB2 are correlated with poor prognosis in breast and ovarian cancer (37,38), but the role of ErbB2 in colon cancer is largely unknown. Our work has suggested a role for ErbB2 in colon cancer because coexpression of ErbB2 and heregulin in colon tumors and cell lines was demonstrated, indicating that constitutive activation of "normal" levels of ErbB2 could provide the signaling basis of tumor growth (39).…”
mentioning
confidence: 99%
“…In one study, the gene encoding the transcription factor GATA4 was identified as one of the 29 overexpressed genes differentially expressed in tumors associated with ERBB2 overexpression (24,25). Interestingly, ERBB2 and GATA4 are essential for cardiovascular development (26)(27)(28) and it has been proposed that GATA4 controls the transcription of critical genes for both differentiation and function of the myocardium. The transcriptional activity of GATA4 is activated via the mitogen-activated protein kinase pathway in cardiomyocytes (29) and the ERBB2 receptor triggers several transduction pathways including the mitogenactivated protein kinase pathway (2).…”
Section: Introductionmentioning
confidence: 99%
“…These free radicals produce peroxidation of myocyte membranes and subsequent influx of intracellular calcium, accelerated degradation of key sarcomeric protein and disruption of new sarcomere protein synthesis. (Valero, 2004; The molecular basis of type II chemotherapy related cardiac dysfunction is beginning to be elucidated (Speyer, 2002;Crone, 2002;Ozcelik, 2002;Sawyer, 2002;Negro, 2004). The mechanism of trastuzumab induced cardiotoxicity involves, at least in part, the ErbB2 pathway.…”
Section: Mechanism Of Cardiotoxicitymentioning
confidence: 99%
“…This agent binds to the extracellular domain of the HER-2 protein and thus blocks ErbB2 signalling required for the growth, repair, and survival of cardiac cells. (Negro, 2004) ErbB2 signalling is highly complex, involving multiple ligand classes, cell systems, and pathway interactions. Of those actions, activation of the transcription factor nuclear-B (NF-B) seems to play an important rule.…”
Section: Mechanism Of Cardiotoxicitymentioning
confidence: 99%